Environmetric study on air quality pattern for assessment in Klang Valley, Malaysia - Sahrir, Syazwani; Abdullah, Ahmad Makmom; Ponrahono, Zakiah; Sharaai, Amir Hamzah (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Air pollution had turned into one of the major environmental issues in Malaysia due to the heavy transportation activities in logistics and automobile dependencies, industrial activities and transboundary pollution from the neighbouring countries. The emission from such events such as infrastructure works, traffic (road, sea, air) and industry are directly responsible for air pollution. The objective of this study was to determine the significant pollutant parameters contributing to air quality issues and to identify air quality pattern at five air monitoring stations in Klang Valley, Malaysia for the years of 2010 until 2014 (five years). This dataset was derived from the Department of Environment, Malaysia (DOE). Air pollution index (API) such as SO2, CO2, NO2, O3, and PM10 were examined in this study. Environmental metric techniques used was cluster analysis (CA) to determine the air quality pattern based on yearly and specific monthly basis. Discriminant analysis (DA) was applied to a distinctive different class. The study identifies that there were different variables or predictors between each class. Principal component analysis (PCA) was used to identify the significant pollutant parameters based on five pollutants in air pollution index (API) which cause by many activities either internal or external factors. This study identified that SO2, CO2, NO2, and PM10 are the primary pollutants contributing to the deteriorating of air pollution in Klang Valley. By using the environmetric technique for analysing the data, it contributes to a better understanding of air quality pattern and clearly identified the vital of atmospheric pollutant parameters.